Going, Going, Gone: Dammed to Die (The Biblical archaeology review, 2020)
In the name of energy production and economic advancement, Turkey has built the Ilisu Dam on the Tigris River. The dam’s reservoir will flood 100 miles of the upstream riverbanks and valleys. Despite the obvious benefits, the dam comes with serious drawbacks. The reservoir will displace thousands of people and destroy the livelihood of […]